2015
DOI: 10.1513/annalsats.201505-267bc
|View full text |Cite
|
Sign up to set email alerts
|

Pyruvate Dehydrogenase Activity is Decreased in the Peripheral Blood Mononuclear Cells of Patients with Sepsis: A Prospective Observational Trial

Abstract: Rationale: Rodent studies have shown that pyruvate dehydrogenase (PDH) levels are low in sepsis. This may cause cells to shift to anaerobic metabolism, resulting in increased lactate production. Alterations in PDH during sepsis have never been studied in humans.Objectives: The objective of this pilot study was to measure PDH activity and quantity in patients with severe sepsis. Methods:We conducted a pilot case-control study at a single urban tertiary care center. We compared PDH activity and quantity between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
25
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 19 publications
5
25
0
1
Order By: Relevance
“…The multiprotein enzyme pyruvate dehydrogenase complex (PDC) is a big, strongly conserved complex that is tightly regulated in activity and is an important sensor of oxygen and a regulator of TCA activity. In sepsis, PDC activity is clearly reduced (Vary, ; Nuzzo et al , ) and several explanations have been provided. PDC needs a co‐factor, thiamin (a.k.a.…”
Section: Sepsis and Mitochondrial Metabolismmentioning
confidence: 99%
“…The multiprotein enzyme pyruvate dehydrogenase complex (PDC) is a big, strongly conserved complex that is tightly regulated in activity and is an important sensor of oxygen and a regulator of TCA activity. In sepsis, PDC activity is clearly reduced (Vary, ; Nuzzo et al , ) and several explanations have been provided. PDC needs a co‐factor, thiamin (a.k.a.…”
Section: Sepsis and Mitochondrial Metabolismmentioning
confidence: 99%
“…Improved mitochondrial function as evidenced by the increased blood pyruvate after fluid resuscitation compared to at admission levels, may explain the reported decreased BLL and L/P ratio especially in survivors and was found to be significant specific predictor for survival. In support of this assumption, Nuzzo et al [44] found pyruvate dehydrogenase (PDH) activity and quantity in septic patients were significantly lower than in healthy controls and in non-survivor compared to survivors and concluded that PDH activity and quantity are low in sepsis, and this may cause cells to shift to anaerobic metabolism, resulting in increased lactate and decreased pyruvate production.…”
Section: Discussionmentioning
confidence: 98%
“…8,9 Third, PDH values may be depressed as a direct consequence of critical illness. 10,11 Finally, thiamine is a key cofactor for PDH. Previous studies have shown that thiamine deficiency is common in both type 1 and type 2 diabetes 12,13 and in patients with DKA.…”
Section: Discussionmentioning
confidence: 99%